2021
DOI: 10.1101/2021.12.21.21268110
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The health effects of Chunga Dumpsite on surrounding communities in Lusaka, Zambia

Abstract: Background: Dumpsites in low and middle income countries (LMICs) are commonly used for solid waste disposal as opposed to landfills. However, these are naturally unsanitary hence provide ideal conditions for breeding of disease transmitting agents and become predisposing factors for spread of diseases and infections to surrounding communities. This study aimed at determining the Health Effects of Chunga Dumpsite on surrounding communities in Lusaka, Zambia. Design and Methods: This was a mixed method des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
(5 reference statements)
1
4
0
Order By: Relevance
“…The dumpsites were highlighted as causing environmental (e.g., pollution) and social impacts (e.g., hazardous working conditions) (P4, P10, P14). This reinforces existing concerns, such as Chibwe et al (2021) who found that communities in the vicinity of the Chunga site suffer high incidences of illness (e.g., malaria, respiratory disease, diarrhea).…”
Section: The Status and Relevance Of Ce Concept 421 Status Of Waste M...supporting
confidence: 86%
See 1 more Smart Citation
“…The dumpsites were highlighted as causing environmental (e.g., pollution) and social impacts (e.g., hazardous working conditions) (P4, P10, P14). This reinforces existing concerns, such as Chibwe et al (2021) who found that communities in the vicinity of the Chunga site suffer high incidences of illness (e.g., malaria, respiratory disease, diarrhea).…”
Section: The Status and Relevance Of Ce Concept 421 Status Of Waste M...supporting
confidence: 86%
“…There are a handful of peer-reviewed studies covering municipal waste management issues. For example, studies have sought to understand the ecological and public health externalities caused by inadequate waste regimes (Chibwe et al, 2021;Muleya et al, 2021). While, in terms of social research, Chileshe and Moonga (2019) critically discuss the political factors behind lagging progress of the "Keep Zambia Green, Clean, and Healthy Campaign. "…”
Section: The Ce In Zambiamentioning
confidence: 99%
“…Further, these people were mainly self-employed with a monthly income of less than US$150. Majority of them had attained primary and secondary education and this is in line with the government's policy on Universal Free Primary Education Policy which envisioned to curb illiteracy, inaccessibility, unaffordability, inequality and high dropout rates in school [19,20]. Hence, it is assumed that this population group is literate enough to respond positively to health education campaigns on prevention of disease outbreaks and respecting the international guidelines on safe distance to the dumpsite [21].…”
Section: Discussionmentioning
confidence: 90%
“…For instance, a study Magongwa (2008) at the University of Witwatersrand revealed high levels of academic competiveness among the deaf and hard of hearing students, whereas a study conducted by Nonde(2013) on academic performance of learners with hearing impairments from Solwezi and Munali secondary schools in Zambia indicated that 63% of the learners' academic performance was below 40% pass mark. Similarly, a study by Chibwe (2013) indicated negative academic performance for learners with hearing impairments, whereas a study by Chibuye (2013) reported that learners with hearing impairments were unable to achieve high scores in reading and writing.…”
Section: Introductionmentioning
confidence: 99%